CHADEMA's 2020 Presidential Election Defeat: Opposition Challenges and CCM's Dominance in Tanzania. - Antony Samsony; Sri Budi Eko Wardani (Universitas Warmadewa, 2025)
The analysis investigates the structural obstacles and strategic shortcomings of opposition parties in Tanzania by studying CHADEMA's defeat during the 2020 presidential election and identifying the reasons behind CCM's ongoing political dominance. The study examines how state-undertaken institutions together with electoral processes alongside media bias and bureaucratic procedures create disadvantages for opposition parties while analyzing their internal weaknesses that include ineffective organization and weak grassroots mobilization and inadequate strategic planning. The central question is. Democratic erosion in Tanzania exists through a combination of institutional barriers coupled with shortcomings in opposition parties. The study evaluates electoral information alongside voter conduct and legal structures using empirical evidence while incorporating observations from political officials. The study demonstrates how CCM's dominance of state institutions combined with its control of electoral authorities produces a systematic disadvantage for opposition parties paired with CHADEMA's organizational flaws that reduce its chances of electoral success. The voting patterns across Tanzania's regions demonstrate significant imbalances in opposition backing because of institutional biases and uneven grassroots efforts. This study advances theoretical knowledge about political opposition and democratic backsliding through its findings showing incumbent parties utilize institutional resources to reinforce their power base (Mettler & Lieberman, 2020). The situation demands three changes which include electoral system improvements together with enhanced opposition party capabilities and active international observation of elections to halt Tanzania's democratic deterioration. The analysis has implications for political systems that maintain weaker opposition parties against powerful governing institutions.